The relationship between HIV infection and acute deep vein thromboses. - Louw, Susan (My University, 2012)
Objective: HIV infection is a global pandemic with approximately 37 million adults infected worldwide.1 Numerous abnormalities predisposing to a hypercoagulable state have been described in patients with HIV infection and include deficiencies of antithrombotic proteins and the presence of procoagulants. The abnormalities have been described to correlate with the degree of HIV associated immunosuppression as well as with the presence of concomitant infections and / or neoplastic disorders. The conclusion of several studies2-3 has been that although evidence pointed towards a relationship between HIV infection and venous thrombotic disease, more studies were indicated to further elucidate this link. The majority of studies reporting on the documented prothrombotic abnormalities in HIV infection were conducted in first world cohorts. The objective of the study was to determine the prevalence of underlying HIV infection in patients presenting with acute deep vein thrombosis (DVT) without the presence of traditional risk factors for DVT. This prevalence was compared to the HIV prevalence in a sex, age and race matched control group without symptomatic DVT. In addition, the possible pathophysiological mechanisms for DVT development in this cohort are detailed. Methods: Consecutive adult patients presenting to the Charlotte Maxeke hospital casualty with lower limb acute deep vein thrombosis (DVT) were invited to participate in the study. Voluntary HIV testing of the participants were performed after counselling and consent with appropriate referral for further management if HIV result was positive. A record review was performed and information regarding the presence of commonly encountered traditional risk factors for the development of DVTs. The control group was an age, sex and race matched cohort to establish the prevalence of HIV infection in a matched population without symptomatic DVTs. A review of the literature to identify the possible underlying causative factors linking HIV and DVT was conducted. Results: The HIV prevalence in the DVT group who consented to HIV testing and who had no traditional risk factor for DVT development (22 patients) was 81% (95% CI 0.67 - 0.96). The HIV prevalence in a matched control group without symptomatic DVTs was found to be 4% (95% CI 0.039 – 0.041). All the DVT patients who consented to HIV testing were active, community integrated members of the society. The average CD4 cell count of the HIV positive patients with acute DVTs was 247 /mm3. Two of the HIV positive patients with DVTs were on ART (anti-retroviral therapy) and 4 were also diagnosed with pulmonary tuberculosis. Traditional DVT risk factors identified in the HIV infected DVT cohort other than tuberculosis were immobilisation and carcinoma. Conclusion: A prothrombotic state is present in HIV infected individuals giving rise to an increased prevalence of thrombotic complications with potentially fatal consequences. The risk of DVTs in the general population is 0.10 % a year2 but the current and other studies indicate that the prevalence in HIV positive patients is significantly increased. From this thesis it is clear that there is no available evidence evaluating thromboprophylaxis specifically in HIV-infected individuals. The available thrombosis treatment guidelines lack recommendations in this growing sub-population. Important treatment decisions are therefore left to medical attendants without clear guidelines. HIV infection in the ARV era is a chronic disease with a clearly prothrombotic tendency. Future studies and guidelines should further define the thrombotic risk in the HIV infected population and direct treatment and prophylaxis.